2009
DOI: 10.1161/atvbaha.108.182519
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Observation of Mechanically-Injured Mouse Femoral Artery Reveals an Antiinflammatory Effect of Renin Inhibitor

Abstract: Objective-The renin-angiotensin-aldosterone system (RAS) plays a central role in atherosclerosis. To investigate the effects of a direct renin inhibitor aliskiren on vascular inflammation, we conducted leukocyte adhesion assays in vivo and in vitro using a novel real-time imaging system. Methods and Results-Aliskiren (10 mg/kg/d) or PBS was administered to C57BL/6 mice (6 -7 weeks of age; Oriental Yeast, Tokyo, Japan) for 2 weeks via an osmotic pump. Blood pressure was not significantly changed in the 2 groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 43 publications
3
34
0
Order By: Relevance
“…In the present study, aliskiren attenuated the intense pro-inflammatory profile in retina of Ren-2 rats with diabetes or OIR, with a reduction in leucostasis, ICAM-1 production and ED-1 immunolabelling to control levels. There is evidence that aliskiren reduced the macrophage content of atherosclerotic plaques [30], leucocyte adhesion in femoral arteries [31] and the number of CD11b + and CD11c + antigen presenting cells in a model of multiple sclerosis [32]. The results of the present study are consistent with these findings, and highlight the potent anti-inflammatory properties of aliskiren.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, aliskiren attenuated the intense pro-inflammatory profile in retina of Ren-2 rats with diabetes or OIR, with a reduction in leucostasis, ICAM-1 production and ED-1 immunolabelling to control levels. There is evidence that aliskiren reduced the macrophage content of atherosclerotic plaques [30], leucocyte adhesion in femoral arteries [31] and the number of CD11b + and CD11c + antigen presenting cells in a model of multiple sclerosis [32]. The results of the present study are consistent with these findings, and highlight the potent anti-inflammatory properties of aliskiren.…”
Section: Discussionsupporting
confidence: 89%
“…The anti-inflammatory effect of aliskiren has been supported by many researches, Jun et al, in 2009 demonstrated that renin inhibition by aliskiren significantly reduced the expression of VCAM-1 and ICAM in injured arteries, also he found that the expression of NF-k B, was attenuated by aliskiren [45]. In addition, Alessandra et al, showed that aliskiren down-regulates TNF-α-stimulated TF expression in HUVECs.…”
Section: Discussionmentioning
confidence: 95%
“…The dose of aliskiren was determined according to previous studies. 20,21 Renal artery constriction (RAC) was performed by making dorsal, longitudinal incisions to expose the kidneys. The trunk of the left renal artery, which showed visible renal ischemia, was constricted by a vascular clamp (0.4-1.0 mm; S&T Fine Science Tools, North Vancouver, B.C.…”
Section: Animal Modelmentioning
confidence: 99%